Recent Advances in Forensic Toxicology - D, Balaji; Panga, Surya Kiran; Dubey, Harshita; Anandani, Garima; Merla, Sathya Veera; Anupurba, Shilpa; Modi, Mansi; Bhankhodia, Vaishali; Sharma, Anil; Ranjan, Amar; Yadav, Abhishek; Kumari, Namita; et al. (Medical Science: Recent Advances and Applications Vol. 4, 2025)
Forensic toxicology has undergone significant advancements in recent years, revolutionising the field of medicolegal death investigation. This chapter explores the major technological developments in forensic toxicology and their implications in determining the cause and manner of death. High-resolution mass spectrometry (HRMS) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) have greatly enhanced the detection and quantification of various substances, including novel psychoactive substances, in biological samples. Dried blood spot (DBS) analysis has emerged as a valuable tool that offers reliable results from minimal and easily stored samples. The integration of metabolomics and toxicogenomics has provided a comprehensive understanding of biochemical changes caused by toxic exposure, enabling the identification of specific biomarkers associated with toxins or drugs. These advancements have led to a more accurate determination of the cause and manner of death, particularly in cases involving complex drug interactions, metabolic disorders, and environmental factors. However, the interpretation of toxicological data remains challenging, requiring a multidisciplinary approach and consideration of factors such as postmortem redistribution and individual variations in drug metabolism. Histopathology plays a crucial role in confirming toxicological findings, identifying target organs affected by toxicity, and providing insight into the nature and duration of toxic exposure. The combination of analytical techniques and microscopic examination has proven to be invaluable in drug-related fatalities and other forensic investigations. As the field continues to evolve, standardised protocols, continuous education, and collaboration among forensic experts are essential to ensure the accurate and reliable determination of the cause of death.